2016
DOI: 10.1002/ppul.23609
|View full text |Cite
|
Sign up to set email alerts
|

Foreign body removal in children: Recommendations versus real life—A survey of current clinical management in Germany

Abstract: Published data shows that rigid bronchoscopy involves fewer complications and is more successful in foreign body removal in children. It is consequently questionable, why 20% of the medical centers report a preference for the flexible method. One reason might be the poor availability of rigid bronchoscopy and the difficulty gaining sufficient expertise in rigid bronchoscopy in Germany. Pediatr Pulmonol. 2017;52:656-661. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 19 publications
0
34
0
1
Order By: Relevance
“…In children with a history of choking, a preceding flexible bronchoscopy reduces the rate of negative rigid bronchoscopies [72,73]. In recent years, flexible bronchoscopy has increasingly been used for foreign body extraction [74]. There is growing evidence that flexible bronchoscopes can be used as a removal tool (either alone or in combination with a rigid bronchoscope), using biopsy or grasping forceps, or wire baskets, with varying success rates [75][76][77][78].…”
Section: Boxmentioning
confidence: 99%
See 1 more Smart Citation
“…In children with a history of choking, a preceding flexible bronchoscopy reduces the rate of negative rigid bronchoscopies [72,73]. In recent years, flexible bronchoscopy has increasingly been used for foreign body extraction [74]. There is growing evidence that flexible bronchoscopes can be used as a removal tool (either alone or in combination with a rigid bronchoscope), using biopsy or grasping forceps, or wire baskets, with varying success rates [75][76][77][78].…”
Section: Boxmentioning
confidence: 99%
“…Attempts to extract foreign bodies using a cryoprobe have been reported [79]; however, in children this technique has been associated with a high rate of complications [80]. If a flexible bronchoscope is used for foreign body extraction, immediate availability of a rigid instrument has been repeatedly recommended to guarantee safety of the procedure in case extraction attempts fail or complications occur [74,75].…”
Section: Boxmentioning
confidence: 99%
“…Rigid bronchoscopy does provide a secure airway and optimal ventilation during foreign body removal 6–8 . Recently flexible bronchoscopy has increasingly been used for foreign body extraction, especially in cases where the foreign body is located in the distal airways 9 . Foreign bodies are removed with flexible bronchoscopes with the aid of biopsy or grasping forceps, and wire baskets, with varying success rates 10–13 .…”
Section: Discussionmentioning
confidence: 99%
“…Foreign bodies are removed with flexible bronchoscopes with the aid of biopsy or grasping forceps, and wire baskets, with varying success rates 10–13 . Availability of a rigid instrument is recommended when extraction of foreign bodies with flexible bronchoscopy is attempted 9,10 . The person responsible for the removal of the foreign body and chosen method of removal differs in different parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that whatever method is used, an immediate switch to rigid bronchoscopy must be possible at least for potentially asphyxiating foreign bodies. An editorial by Kazachkov and Vicencio concluded that many questions regarding the equivalence of flexible bronchoscopy to the rigid technique have never been evaluated in a prospective manner, and many questions regarding the use of cryoprobes remain unanswered. They recommended establishment of formal courses for interventional bronchoscopy in children, following the example of adult pulmonology.…”
Section: Diagnostic Testing/endoscopymentioning
confidence: 99%